2019
DOI: 10.1016/j.ijhydene.2019.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Operation of solid oxide fuel cells with alternative hydrogen carriers

Abstract: Future electricity production will use fossil-free sources with zero CO2 emission or closed carbon cycle technologies based on renewable sources. While hydrogen is considered a key energy source, its production at present time relies heavily on fossil fuels. Furthermore, distribution and storage are not well established and require substantial investments. This is a strong motivation to identify alternative, safe, high power density hydrogen carriers, where existing logistics and infrastructure can be utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 21 publications
0
56
1
2
Order By: Relevance
“…5% degradation was observed when ammonia fuel was supplied to an SOFC short stack consisting of 10 planar cells. Also, this is superior to the value reported by Hagen et al [22], where degradation by 2-4% kh -1 was reported in a single cell (53 53 mm 2 ) with pure ammonia fuel at 850°C.…”
Section: 000 H Durability Testcontrasting
confidence: 79%
See 3 more Smart Citations
“…5% degradation was observed when ammonia fuel was supplied to an SOFC short stack consisting of 10 planar cells. Also, this is superior to the value reported by Hagen et al [22], where degradation by 2-4% kh -1 was reported in a single cell (53 53 mm 2 ) with pure ammonia fuel at 850°C.…”
Section: 000 H Durability Testcontrasting
confidence: 79%
“…Also, this is superior to the value reported by Hagen et al. , where degradation by 2–4% kh −1 was reported in a single cell (53 × 53 mm 2 ) with pure ammonia fuel at 850 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coupled with combined heat and power system (CHP), the SOFC efficiency can reach up to 90% [2,3]. The key distinction between SOFCs and low-temperature fuel cells is that aside from pure hydrogen the former can operate with alternative fuels, including bio-hythane [4,5], ethanol [6][7][8], kerosene [9], propane [10][11][12], ammonia [13,14], syngas [15], methane [16][17][18][19][20], and biogas [14,[21][22][23][24][25][26], where CO also serves as a reactant in the electrochemical reactions [14,19,[27][28][29]. This ability is a remarkable advantage given the high cost of pure hydrogen required in low-temperature fuel cells although when hydrogen produced from renewable energy [30,31].…”
Section: Introductionmentioning
confidence: 99%